2006
DOI: 10.1007/s11172-006-0546-y
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 3-nitro-2-trihalomethyl-2H-chromenes with C-nucleophiles. Synthesis of 3-nitro-4-(pyrazol-4-yl)-2-trihalomethylchromanes

Abstract: The nucleophilic addition of acetylacetone and ethyl acetoacetate at the double bond of 3 nitro 2 trihalomethyl 2H chromenes in the presence of NaH affords 2,3,4 trisubstituted chromanes containing the β dicarbonyl fragment at position 4. The trans-trans configuration and the enol structure of the reaction products were confirmed by 1 H NMR spectroscopy and X ray diffraction. Treatment of these compounds with hydrazine gives the corresponding 3 nitro 4 (pyrazol 4 yl) 2 trihalomethylchromanes. The reactions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Joergensen et al reported that severe vitamin D deficiency was not associated with UACR in two prospective observational follow-up studies. 37,38 We analyzed the researches that are inconsistent with our findings. We speculated that the different results might be due to the following factors: 1) the study population and methods were diverse.…”
Section: Subgroup and Interaction Analysismentioning
confidence: 65%
“…Joergensen et al reported that severe vitamin D deficiency was not associated with UACR in two prospective observational follow-up studies. 37,38 We analyzed the researches that are inconsistent with our findings. We speculated that the different results might be due to the following factors: 1) the study population and methods were diverse.…”
Section: Subgroup and Interaction Analysismentioning
confidence: 65%
“…Kodess et al. utilized the direct alkylation strategy for accessing chromanes containing the β-dicarbonyl fragment at position C4 by the nucleophilic addition of acetylacetone and ethyl acetoacetate at the double bond of 3-nitro-2 H -chromenes . Some similar strategies were disclosed to obtain functionalized Michael adducts using activated methylene such as malonates and ketones .…”
mentioning
confidence: 99%